The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1111/j.1365-2648.2005.03591.x
|View full text |Cite
|
Sign up to set email alerts
|

How is the indoor environment related to asthma?: literature review

Abstract: There is some evidence of a link between the indoor environment and asthma. There are measures, which could be promoted by healthcare professionals to alleviate asthmatic symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
69
2
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(79 citation statements)
references
References 64 publications
5
69
2
3
Order By: Relevance
“…Hundreds of mould species are found indoors. Common genera are Alternaria, Cladosporium, Aspergillus, Penicillium and Fusarium [4]. The presence of water, nutrients or elevated temperature facilitates the proliferation of moulds, cockroaches and mites, thus increasing the concentration of allergens.…”
Section: Indoor Air Pollutants and Relative Sourcesmentioning
confidence: 99%
“…Hundreds of mould species are found indoors. Common genera are Alternaria, Cladosporium, Aspergillus, Penicillium and Fusarium [4]. The presence of water, nutrients or elevated temperature facilitates the proliferation of moulds, cockroaches and mites, thus increasing the concentration of allergens.…”
Section: Indoor Air Pollutants and Relative Sourcesmentioning
confidence: 99%
“…It is estimated that up to 66% of time is spent at home and that this percentage is likely to be higher among pre-school children (Leech et al, 2002). Modern household living conditions that incorporate higher levels of insulation, central heating and poor air circulation are implicated in the increased rates of childhood asthma in the UK (Lindfors et al, 1995;Jones, 1998;Richardson et al, 2005). Previous studies have shown that a number of factors in the home environment can act as triggers to asthma.…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that 1 in 10 children in the UK now have the disease (Anderson et al, 2004;Richardson et al, 2005), and that rates in seven-and eight-year olds increased by 5% between 1991 and 2002 (Butland et al, 2006). Asthma is more common in boys (Diette et al, 2007) and in those living in socioeconomically disadvantaged communities (Wu and Takaro, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indoor temperature and humidity not only influence surface condensation, mould growth, and the occupant's health such as allergies, skin disease, and respiratory disease but also structural problems such as heat and moisture behavior inside the structure (Fedorik et al, 2015;Richardson et al, 2005;Mudarri and Fisk, 2007). Therefore, in this paper, a simulation was used to analyze the hygrothermal performance of the wall according to the position of internal and external insulation in wood frame houses.…”
Section: Introductionmentioning
confidence: 99%